The two gentlemen of Verona / notes by K. Deighton - Shakespeare, William; Deighton, K.; Barter Theatre (Organization : Abingdon, Va.); Theater Playbills and Programs Collection (Library of Congress) (London : Macmillan and co., 1953)
Robert Porterfield presents "The Two Gentlemen of Verona," by William Shakespeare, designed and directed by John Edward Friend, lighting by Albin Aukerlund.
Includes bibliographical refereneces and index.
In: American theater programs of the late 19th and 20th centuries (Library of Congress).
Keywords: English drama; Theater programs -- Virginia -- Abingdon; Theater programs -- 1953.